Pengaruh Kegiatan Ekstrakurikuler Kepramukaan Terhadap Kedisiplinan Siswa di SD Negeri Krueng Raya Desa Meunasah Mon Kecamatan Mesjid Raya Kabupaten Aceh Besar - Rina Afriana; soedirman Soedirman; Said Darnius (Universitas Syiah Kuala, 2022)
Discipline is one of the attitudes that requires a person to be responsible for his behavior, to instill discipline not only to control the learning process in the classroom. Therefore, additional activities are needed to support their achievement, such as scouting activities. The formulation of the problem in the research is whether there is an effect of scouting activities on the discipline of the students of SD Negeri Krueng Raya, Meunasah Mon Village, Mesjid Raya District, Aceh Besar Regency. The purpose of this study was to determine the effect of scouting activities on student discipline at SD Negeri Krueng Raya, Meunasah Mon Village, Mesjid Raya District, Aceh Besar Regency. The approach in this research is quantitative. The sample is 25 students from grades 4 and 5 who are actively involved in scouting extracurricular activities. The method of data collection is in the form of a questionnaire. The data obtained in this study used the product moment formula. Where the results in this study indicate that there is an influence between scouting activities on student discipline at SD Negeri Krueng Raya, Meunasah Mon Village, Mesjid Raya District, Aceh Besar Regency. This is evident from the data analysis using the product Moment formula. And calculating df especially df = n - 2 = 25 - 2 = 23 can prove the results of r table. With the results of the r table value with a significant level of 5% = 0.413 and the calculated r value = 0.473, then the r-count result is greater than the r-table value, namely 0.473 0.413. The hypothesis that the researchers got was that there was an influence of scouting activities on student discipline at SD Negeri Krueng Raya, Meunasah Mon Village, Masjid Raya District, Aceh Besar Regency, which was accepted.